THE RELATIONSHIP OF KNOWLEDGE ABOUT FEVER SEIZURES AND MOTHER'S ATTITUDES IN PREVENTING FEVER SEIZURES INTODDLER AGES 6 MONTHS - 4 YEARS AT LETWARU HEALTH CENTER - Sari, Wahyu Anjas; Sumini, Gempi Tri (Jurnal Medika Cendikia, 2024)
Lack of knowledge and attitudes of mothers about the symptoms and process of febrile seizures results in increased infant mortality. This study aims to determine the relationship between knowledge and maternal attitudes in preventing febrile seizures in toddlers aged 6 months - 4 years at the Letwaru Health Center. The design of this research is cross sectional analysis. The population of this study was 368 people. The sample in this study was 37 people. Sample selection was carried out using simple random sampling. Data collection uses a questionnaire. Data were analyzed using the Mann Whitney statistical test. The research results showed that the majority of respondents had good knowledge, namely 19 people (51.4%), the majority of respondents had a positive attitude, namely 26 respondents (70.3%). From the results of statistical tests using the Mann Whitney test, a significance result of 0.000 <0.05 was obtained, which means there is a relationship between knowledge about febrile seizures and mothers' attitudes in preventing febrile seizures in toddlers aged 6 months - 4 years. There needs to be an increase in knowledge and a change in mothers' attitudes to provide explanations and health education in preventing febrile seizures in toddlers so that mothers are correct in preventing febrile seizures.